A Kinetic Comparison between Laboratory and Industrial Scales in the Copper Blowing Process. (16th June 2009) - Roselló, A.; Martínez, J.; Carrillo, F.
Abstract : An experimental investigation into the oxidation kinetics of molten sulfide has been conducted at laboratory scale to provide information concerning the influence of the gas feed (flow and oxygen pressure) and melt temperature on the desulfurization rate. Data showed that the reaction rate was strongly dependent on the gas flow rate and significantly from oxygen pressure, whereas the influence of temperature was negligible. The variation of the sulfur conversion with the operation time was similar to that found in industrial trials when "white metal" was blown to blister copper in a Peirce-Smith converter. A unique equation for both scales could be established. This correlation made it possible to calculate the operation time in the converter at different gas flow rates and oxygen enrichments.